2019
DOI: 10.1038/s41598-019-38783-5
|View full text |Cite
|
Sign up to set email alerts
|

Traditional risk factors for essential hypertension: analysis of their specific combinations in the EPIC-Potsdam cohort

Abstract: Appropriate interventions might improve the prevention of essential hypertension. This requires a comprehensive view of modifiable lifestyle factors (MLFs) distribution and effect. To determine how six MLFs (general adiposity, abdominal adiposity, alcohol consumption, smoking, diet, physical inactivity) for risk of hypertension are distributed and how their combinations affect the risk, a prospective study cohort of 11,923 healthy participants from the population-based European Prospective Investigation into C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
2
11
0
3
Order By: Relevance
“…This finding is similar to those of previous HLI studies that examined the associations between individual factors and hypertension [9][10][11][12][13]. This result also accords with those reported by Andriole et al [27], who investigated how combinations of six modifiable lifestyle factors (i.e., BMI, waist circumference, physical activity, smoking, alcohol consumption, and diet) are differentially linked with the incidence of hypertension in a large German cohort, and found that being overweight or obese (BMI �25 kg/m 2 ) contributed the most to hypertension risk among the six lifestyle factors. The present study adds to evidence that obesity plays a major role in the development of hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is similar to those of previous HLI studies that examined the associations between individual factors and hypertension [9][10][11][12][13]. This result also accords with those reported by Andriole et al [27], who investigated how combinations of six modifiable lifestyle factors (i.e., BMI, waist circumference, physical activity, smoking, alcohol consumption, and diet) are differentially linked with the incidence of hypertension in a large German cohort, and found that being overweight or obese (BMI �25 kg/m 2 ) contributed the most to hypertension risk among the six lifestyle factors. The present study adds to evidence that obesity plays a major role in the development of hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…Although major final outcome of CVD such as death and cardiovascular disability do not occur in hypertensive children, they are encountered with increased risk of intermediate markers of target organ damage, such as left ventricular hypertrophy, retinal vascular changes, thickening of the carotid vessel wall, and even subtle cognitive changes [4]. It is widely recognized that blood pressure levels are influenced by genetic as well as by environmental factors [5,6]. In this regard, more than 90 different genetic polymorphisms have been identified to be associated with high blood pressure [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, more than 90 different genetic polymorphisms have been identified to be associated with high blood pressure [7]. For example, a recent study reported that polymorphism of aldosterone synthase gene is linked with the development of hypertension through increasing the aldosterone level and aldosterone/renin ratio [5]. On the other hand, among environmental parameters, obesity, smoking, alcohol consumption, diet, and physical inactivity likely play a major role in development of hypertension [6].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of such interventions requires an understanding of modifiable lifestyle factors. A study conducted in Germany in 2019 identified six well-recognised high-risk, modifiable lifestyle factors for hypertension [13]. General and abdominal adiposity, smoking and physical inactivity play important roles in increasing the risk of incidence and lack of control of hypertension.…”
Section: Introductionmentioning
confidence: 99%